Going into COP26 and getting it right: Forests, agriculture, ecosystems and nature for climate change mitigation and adaptation - Martius, C.; Leonard, S.; Sarmiento Barletti, J.P.; Djoudi, H.; Prabhu, R. (Center for International Forestry Research, 2021)
Forests, trees and the transformation of agriculture remain a proven mitigation and adaptation pathway, which must receive substantially more support in terms of funding and capacity development. Protecting and restoring habitats is a powerful way to boost resilience to the impacts of climate change.